THE RELATIONSHIP BETWEEN TWO ANT SPECIES WORKERS, APHIDS NYMPHS AND THE APHIDS BEING PARASITIZED ON IN THE CASE OF BROAD BEAN PLANTS - Suaad I. Abdullah (Mesopotamia Journal of Agriculture)
Monomorium sp. ant species were found on Broad Bean plants planted in 2004. The highest avarages of the workers and nymphs of Broad Bean aphids Aphis sp. which recorded 21.91 worker and 514.80 nymph in the middle of April in 2004, a positive-significant corelation between the previous mentioned ant species and Broad Bean nymphs. In 2005 the highest averages of another species of ant workers of Tapinoma simrothi Krausse aphid nymphs and aphid being parasitized on were recorded on Broad Bean plants at the end of March which reached 22.25 worker, (476.10 and 129.42) nymph for each one of them respectively a positive-significant relationship with high rate of significance between the previously mentioned ant workers and the Broad Bean nymphs had been noticed.